Reducing and preventing internalizing and externalizing behavior problems in children with type 1 diabetes: a randomized controlled trial of the Triple P‐Positive Parenting Program. Issue 7 (29th August 2014) - Westrupp, EM; Northam, E; Lee, KJ; Scratch, SE; Cameron, F
Abstract Background Children with type 1 diabetes are at increased risk of mental health problems, which in turn are associated with poor glycemic control, diabetes‐related complications, and long‐term psychiatric morbidity. We tested the efficacy of the Triple P‐Positive Parenting Program in reducing or preventing mental health problems and improving glycemic control in children with type 1 diabetes in a randomized controlled trial. Methods Participants were recruited from the Diabetes Clinic, Royal Children's Hospital, Melbourne, Australia, and randomized to Triple P or standard diabetes care. The primary outcome was child internalizing and externalizing behavior problems 3 and 12 months postrandomization. Secondary outcomes were glycemic control, parent mental health, parenting skills, and family functioning at 3 and 12 months, and glycemic control at 24 months. Results A total of 76 participants were randomized (38 to intervention and 38 to control), 60 completed 3‐month, and 57 completed 12‐month assessments. Benefits of Triple P were evident at 3 months for parent mental health, parenting skills, and family functioning (p < 0.05), but not for child mental health or glycemic control, with little effect at 12 months. Prespecified subgroup analyses for children with pre‐existing internalizing or externalizing behavior problems indicated greater improvements in child mental health, parent mental health, parenting skills, and diabetes family conflict (p < 0.05), but lower parenting self‐efficacy at 3 months. Improvements in parent mental health and parenting competency associated with Triple P were sustained to 12 months for children with pre‐existing mental health problems. Conclusions This study provides some support for the efficacy of Triple P in improving parent and family outcomes, and reducing child internalizing and externalizing behavior problems primarily in children who have pre‐existing mental health problems.